Preparation method and application of organic modified vanadium oxide composite material

By mixing the aqueous vanadium pentoxide solution with organic monomers containing reducing groups and carrying out hydrothermal reactions to prepare organic modified vanadium oxide composites, the problems of low efficiency and serious capacity decay during low current cycle of water-based zinc-iodine batteries are solved, and efficient cycle stability and rate performance are achieved.

CN119181796BActive Publication Date: 2025-04-01PETROCHINA SHENZHEN NEW ENERGY RESEARCH INSTITUTE CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411677578.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-04-01
Estimated Expiration
2044-11-22

AI Technical Summary

Technical Problem

The water-based zinc-iodine battery has low efficiency when cycling of small currents and has severe capacity attenuation, making it difficult to achieve a reversible and stable charge and discharge cycle.

Method used

The aqueous vanadium pentoxide solution is mixed with organic monomers containing reducing groups, and the high-valent vanadium is reduced in situ through hydrothermal reaction to form an organic-modified vanadium oxide composite material, and the organic matter is evenly distributed on the surface of vanadium dioxide to enhance the structural stability of the material.

Benefits of technology

The initial specific capacity reached 338 mAh/g at a current density of 0.1 A/g, and the specific capacity of 333 mAh/g was maintained after 55 weeks of cycle, which significantly improved the Coulomb efficiency and cycle stability of the aqueous zinc-iodine battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181796B_ABST
    Figure CN119181796B_ABST
Patent Text Reader

Abstract

The present invention discloses a preparation method and application of an organic modified vanadium oxide composite material, which relates to the field of electrochemical energy storage technology, and comprises the following steps: mixing a vanadium pentoxide aqueous solution with an organic monomer to obtain a solution A; subjecting the solution A to a hydrothermal reaction, collecting the solid-liquid mixture, washing and drying, and obtaining an organic modified vanadium oxide composite material; wherein the organic monomer is an organic monomer containing a reducing group. In the present invention, the organic modified vanadium oxide composite material is prepared by in-situ reduction of high-valent vanadium by a liquid phase reduction method; when applied to the positive electrode of an aqueous zinc-iodine battery, the organic modified vanadium oxide composite material can catalyze the conversion of a reversible reaction between polyiodide ions / iodine elements while exerting its own capacity, achieving an initial specific capacity of 338 mAh / g at 0.1 A / g, and maintaining a specific capacity of 333 mAh / g after 55 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to a method for preparing an organic-modified vanadium oxide composite material and its application in the field of energy storage batteries. Background Art

[0002] Aqueous zinc-ion batteries (AZIBs) are currently a hot research area for secondary batteries. Water-based electrolytes are highly safe, and abundant zinc metal resources are highly economical. Therefore, aqueous zinc-ion batteries are expected to become an alternative solution in the field of large-scale energy storage. The internal structure of aqueous zinc-ion batteries consists of a positive electrode, a zinc negative electrode, a separator, and an electrolyte. Among them, the positive electrode materials mainly include vanadium oxide, manganese oxide, organic matter, Prussian blue, etc. Manganese oxide faces serious electrode material dissolution problems due to the Jahn-Teller effect, while organic matter and Prussian blue materials are at a disadvantage in the current "high specific energy" battery demand competition due to their low specific capacity. Therefore, vanadium oxide with high specific capacity has become a promising positive electrode material for AZIB.

[0003] In order to further increase the working voltage and discharge capacity of the vanadium oxide positive electrode, I is often added to the electrolyte. - To provide I - / I2 redox couple method to achieve high-performance aqueous zinc-ion batteries based on dual energy storage mechanism. However, the resulting shuttle effect of multiple iodide ions makes aqueous zinc batteries face low coulombic efficiency and serious capacity decay problems during low current cycling, making it difficult to achieve reversible and stable charge and discharge cycles. Summary of the invention

[0004] The main purpose of the present invention is to provide a preparation method of an organic-modified vanadium oxide composite material and its application, aiming to solve the problem of low coulombic efficiency of existing aqueous zinc-iodine batteries during small current circulation.

[0005] To achieve the above object, the present invention provides a method for preparing an organic-modified vanadium oxide composite material, the method for preparing the organic-modified vanadium oxide composite material comprising the following steps:

[0006] The vanadium pentoxide aqueous solution and the organic monomer are mixed and stirred to obtain a solution A;

[0007] Performing a hydrothermal reaction on solution A, collecting the solid-liquid mixture, washing and drying it, and obtaining an organic-modified vanadium oxide composite material;

[0008] Wherein, the organic monomer is an organic monomer containing a reducing group.

[0009] In one embodiment, the organic monomer includes at least one of 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, p-aminophenol, m-aminophenol and o-aminophenol.

[0010] In one embodiment, in the step of mixing and stirring the vanadium pentoxide aqueous solution and the organic monomer to obtain solution A:

[0011] The concentration of vanadium pentoxide in the vanadium pentoxide aqueous solution is 4-7 mg / mL; and / or,

[0012] The stirring time is 30 to 60 min; and / or,

[0013] In the solution A, the concentration of organic monomers is 2-4 mg / mL.

[0014] In one embodiment, in the step of subjecting solution A to a hydrothermal reaction, collecting the solid-liquid mixture, washing and drying it, and obtaining an organic-modified vanadium oxide composite material:

[0015] The temperature of the hydrothermal reaction is 120-160° C.; and / or,

[0016] The hydrothermal reaction time is 16 to 32 hours; and / or,

[0017] The drying temperature is 60-80°C.

[0018] In one embodiment, before the step of mixing and stirring the vanadium pentoxide aqueous solution with the organic monomer, the method further comprises:

[0019] Add vanadium pentoxide powder into water and stir to obtain a vanadium pentoxide aqueous solution.

[0020] In one embodiment, the purity of the vanadium pentoxide powder is 95% to 99.99%; and / or,

[0021] The stirring time is 10 to 20 min; and / or,

[0022] The stirring speed is 200-400 r / min.

[0023] The present invention also provides an application of the organic-modified vanadium oxide composite material obtained by the preparation method of the organic-modified vanadium oxide composite material as described above in positive electrode materials for aqueous zinc-iodine batteries.

[0024] The present invention also provides a method for preparing a positive electrode material for an aqueous zinc-iodine battery, the method comprising the following steps:

[0025] The organic modified vanadium oxide composite material is mixed with a conductive agent and a binder, and ground, and mixed with an organic solvent to obtain a slurry;

[0026] The slurry is applied onto a current collector and dried to obtain an aqueous zinc-iodine battery positive electrode material;

[0027] Wherein, the organic-modified vanadium oxide composite material is prepared by the above-mentioned preparation method of the organic-modified vanadium oxide composite material.

[0028] In one embodiment, in the slurry, the concentration of the organic-modified vanadium oxide composite material is 20-50 mg / mL.

[0029] In one embodiment, the mass ratio of the organic-modified vanadium oxide composite material, the conductive agent and the binder is (6.5-7): (2-3): (0.5-1); and / or,

[0030] The conductive agent includes at least one of acetylene black, carbon black, conductive carbon black and carbon nanotubes; and / or,

[0031] The binder comprises polyvinylidene fluoride; and / or,

[0032] The organic solvent comprises N-methylpyrrolidone; and / or,

[0033] The current collector includes at least one of carbon cloth and stainless steel mesh.

[0034] In the technical scheme of the present invention, a vanadium pentoxide aqueous solution is mixed with an organic monomer, and a high-valent vanadium is in situ reduced by a liquid phase reduction method to obtain vanadium dioxide, and at the same time, the organic matter is evenly distributed on the surface of the generated vanadium dioxide to obtain a structurally stable organic modified vanadium oxide composite material. When the material is applied to the positive electrode material of an aqueous zinc-iodine battery, the obtained aqueous zinc-iodine battery positive electrode material is not easy to dissolve and fall off during the charge and discharge process, and can achieve an initial specific capacity of 338 mAh / g at a current density of 0.1 A / g, and can still maintain a specific capacity of 333 mAh / g after 55 cycles. The present invention uses the flexible structure of organic matter to coat vanadium oxide, which can effectively inhibit the dissolution of vanadium elements and catalyze the conversion of polyiodine ions / iodine element reactions, thereby improving the energy density and cycle stability of aqueous zinc-iodine batteries based on vanadium oxide-organic positive electrodes. Therefore, the organic modified vanadium oxide composite material prepared by the present invention has the technical effects of low coulombic efficiency, good cycle stability and good rate performance when applied to the positive electrode material of an aqueous zinc-iodine battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0036] Figure 1 This is a scanning electron micrograph of the organic-modified vanadium oxide composite material obtained in Example 1 of the present invention;

[0037] Figure 2 This is the EDS element distribution diagram of all elements in the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention;

[0038] Figure 3 This is an EDS element distribution diagram of vanadium in the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention;

[0039] Figure 4 This is an EDS element distribution diagram of oxygen in the organic-modified vanadium oxide composite material obtained in Example 1 of the present invention;

[0040] Figure 5 This is the EDS element distribution diagram of carbon element in the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention;

[0041] Figure 6 This is an EDS element distribution diagram of nitrogen in the organic-modified vanadium oxide composite material obtained in Example 1 of the present invention;

[0042] Figure 7 This is an X-ray diffraction test diagram of the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention;

[0043] Figure 8 The charge and discharge curves of the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention and the vanadium-based oxide material prepared in Comparative Example 1 at a current density of 0.1 A / g;

[0044] Fig. 9 The charge and discharge curve of the vanadium-based oxide material prepared in Comparative Example 1 of the present invention at a current density of 0.5 A / g;

[0045] Fig.10 This is a test diagram of the cyclic stability of the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention;

[0046] Fig.11 This is a rate performance test diagram of the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention.

[0047] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION

[0048] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components in a certain specific posture. If the specific posture changes, the directional indication will also change accordingly.

[0050] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features limited to "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the "and / or" or "and / or" appearing in the full text include three parallel solutions. Taking "A and / or B" as an example, it includes solution A, solution B, or solutions that satisfy both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0051] Aqueous zinc-ion batteries (AZIBs) are currently a hot research area for secondary batteries. Water-based electrolytes are highly safe, and abundant zinc metal resources are highly economical. Therefore, aqueous zinc-ion batteries are expected to become an alternative solution in the field of large-scale energy storage. The internal structure of aqueous zinc-ion batteries consists of a positive electrode, a zinc negative electrode, a separator, and an electrolyte. Among them, the positive electrode materials mainly include vanadium oxide, manganese oxide, organic matter, Prussian blue, etc. Manganese oxide faces serious electrode material dissolution problems due to the Jahn-Teller effect, while organic matter and Prussian blue materials are at a disadvantage in the current "high specific energy" battery demand competition due to their low specific capacity. Therefore, vanadium oxide with high specific capacity has become a promising positive electrode material for AZIB.

[0052] In order to further increase the working voltage and discharge capacity of the vanadium oxide positive electrode, I is often added to the electrolyte. - To provide I - / I2 redox couple method to achieve high-performance aqueous zinc-ion batteries based on dual energy storage mechanism. However, the resulting shuttle effect of multiple iodide ions makes aqueous zinc batteries face low coulombic efficiency and serious capacity decay problems during low current cycling, making it difficult to achieve reversible and stable charge and discharge cycles.

[0053] At present, some studies have added porous activated carbon to the positive electrode active material to adsorb polyiodide ions, thereby inhibiting the shuttle effect. However, the method has the following defects: (1) The activated carbon has a high mass proportion (greater than 40%), but has no energy storage activity, which reduces the mass energy density of the battery; (2) The vanadium oxide and activated carbon are only simply physically compounded, which is easy to fall off during the cycle, resulting in capacity decay.

[0054] In view of this, the present invention proposes a method for preparing an organic-modified vanadium oxide composite material, comprising the following steps:

[0055] The vanadium pentoxide aqueous solution and the organic monomer are mixed and stirred to obtain a solution A;

[0056] Performing a hydrothermal reaction on solution A, collecting the solid-liquid mixture, washing and drying it, and obtaining an organic-modified vanadium oxide composite material;

[0057] Wherein, the organic monomer is an organic monomer containing a reducing group.

[0058] In the technical scheme of the present invention, a vanadium pentoxide aqueous solution (V2O5) is mixed with an organic monomer, and a high-valent vanadium is in situ reduced by a liquid phase reduction method to obtain vanadium dioxide, and the organic matter is evenly distributed on the surface of the generated vanadium dioxide, so that when applied to the positive electrode material of an aqueous zinc-iodine battery, the obtained aqueous zinc-iodine battery is not easy to dissolve and fall off during the charging and discharging process, and can achieve an initial specific capacity of 338 mAh / g at a current density of 0.1 A / g, and can still maintain a specific capacity of 333 mAh / g after 55 cycles. The present invention uses the flexible structure of organic matter to coat vanadium oxide, which can effectively inhibit the dissolution of vanadium elements and catalyze the conversion of polyiodine ions / iodine element reactions, thereby improving the energy density and cycle stability of aqueous zinc-iodine batteries based on vanadium oxide-organic positive electrodes. Therefore, the organic-modified vanadium oxide composite material prepared by the preparation method of an organic-modified vanadium oxide composite material provided by the present invention has excellent cycle stability and rate performance when applied to the positive electrode material of an aqueous zinc-iodine battery.

[0059] The organic-modified vanadium oxide composite material provided by the present invention has an organic coating on the surface of vanadium dioxide, and enhances the adsorption of polyiodide ions and catalytic conversion of polyiodide ions into elemental iodine through organic molecules containing amino groups, thereby inhibiting the shuttling side reaction of polyiodide ions and enhancing the coulombic efficiency and cycle stability of vanadium-based oxides in aqueous zinc-iodine batteries.

[0060] The present invention does not limit the specific substance of the organic molecule, as long as it contains a reducing group, which can be an amino group, a hydroxyl group, a carbonyl group, etc. When the organic monomer is mixed with the vanadium pentoxide aqueous solution and then subjected to a hydrothermal reaction, the reducing group in the organic monomer can reduce the vanadium pentoxide to vanadium dioxide. In addition, the organic matter can also adhere to the surface of the vanadium dioxide and form an organic-modified vanadium oxide composite material together with the vanadium dioxide, that is, an organic-modified vanadium dioxide composite material.

[0061] In some embodiments, the organic monomer includes at least one of 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, p-aminophenol, m-aminophenol and o-aminophenol. Diaminonaphthalene contains amino groups, and aminophenol contains amino groups and hydroxyl groups. The above substances can not only reduce vanadium pentoxide to vanadium dioxide, but also when the formed organic modified vanadium dioxide composite material is applied to the positive electrode material of aqueous zinc-iodine battery, the organic modified vanadium dioxide composite positive electrode can not only exert its own capacity, but also utilize the hydroxyl or amino groups contained in the organic matter to chemically adsorb polyiodide ions and catalytically convert them into iodine element, thereby improving the specific capacity and cycle stability of the organic modified vanadium dioxide composite positive electrode material in zinc-iodine battery.

[0062] In addition, the hydrothermal method is used to synthesize organic-modified vanadium oxide composites, which has simple steps and high efficiency.

[0063] Firstly, a vanadium pentoxide aqueous solution and an organic monomer are mixed and stirred to obtain a solution A.

[0064] The organic monomer is preferably in powder form. The operation of mixing and stirring the vanadium pentoxide aqueous solution with the organic monomer can be to add the organic monomer powder into the vanadium pentoxide aqueous solution. The powdered organic monomer can be better dispersed in the vanadium pentoxide aqueous solution, fully react with the vanadium pentoxide, and adhere to the surface of the generated vanadium dioxide, so that the obtained organic-modified vanadium oxide composite material has fewer impurities and more uniform distribution of organic matter.

[0065] Further, the concentration of vanadium pentoxide in the vanadium pentoxide aqueous solution is 4-7 mg / mL. Specifically, the concentration of vanadium pentoxide in the vanadium pentoxide aqueous solution can be 4 mg / mL, 5 mg / mL, 6 mg / mL, 7 mg / mL, etc. If the concentration of vanadium pentoxide in the vanadium pentoxide aqueous solution is too low, the mass of the generated product will be small and the production efficiency will be low. 7 mg / ml is close to the maximum solubility of vanadium pentoxide in water at room temperature. Therefore, the concentration of vanadium pentoxide in the vanadium pentoxide aqueous solution is 4-7 mg / mL, which can improve the production efficiency.

[0066] When adding the organic monomers to the vanadium pentoxide aqueous solution and mixing them, stirring can be used to make the mixture more uniform. In some preferred embodiments, the stirring time is 30 to 60 minutes, specifically, the stirring time can be 30 minutes, 40 minutes, 50 minutes, 60 minutes, etc. Too short a stirring time will lead to uneven mixing, which will lead to insufficient subsequent reactions. Therefore, the stirring time of 30 to 60 minutes can make the organic monomers more uniformly mixed in the vanadium pentoxide aqueous solution.

[0067] In one embodiment, the concentration of the organic monomer in the solution A is 2-4 mg / mL. It can be understood that, when the effect of the added organic monomer powder on the volume of the vanadium pentoxide aqueous solution is negligible, adding 2-4 mg of the organic monomer to every 1 ml of the vanadium pentoxide aqueous solution can obtain a structurally stable organic-modified vanadium oxide composite material.

[0068] Then, solution A is subjected to a hydrothermal reaction, and the solid-liquid mixture is collected, washed and dried to obtain an organic-modified vanadium oxide composite material.

[0069] The specific operation of performing a hydrothermal reaction on solution A can be transferring solution A to a hydrothermal reactor for reaction, wherein the temperature of the hydrothermal reaction is 120-160° C., and the time of the hydrothermal reaction is 16-32 hours. Specifically, the temperature of the hydrothermal reaction can be 120° C., 130° C., 140° C., 160° C., etc., and the time of the hydrothermal reaction can be 16 hours, 20 hours, 24 hours, 28 hours, 32 hours, etc. By using the above hydrothermal reaction time and temperature, a structurally stable organic-modified vanadium oxide composite material can be obtained.

[0070] After the hydrothermal reaction is completed, the solid-liquid mixture in the hydrothermal reaction kettle is collected, first centrifuged with water and then centrifuged with ethanol, and the black solid material is collected and dried to obtain an organic-modified vanadium oxide composite material. The drying temperature is 60-80°C, specifically, the drying temperature can be 60°C, 70°C, 80°C, etc. The above drying temperature can dry the black solid material faster without destroying its composition and structure.

[0071] Centrifugal cleaning is an operation that uses centrifugal force to separate solid particles from liquid. Through the high-speed rotating centrifuge, the solid particles in the solid-liquid mixture are subjected to a large centrifugal force, thereby separating them from the liquid. Water or ethanol is used as a flushing medium to remove stains and impurities on the surface of the solid particles.

[0072] Specifically, in some embodiments, the operation of synthesizing the organic-modified vanadium oxide composite material by hydrothermal method is:

[0073] A vanadium pentoxide aqueous solution with a concentration of 4-7 mg / mL and an organic monomer are mixed and stirred for 30-60 min to obtain a solution A, wherein the concentration of the organic monomer in the solution A is 2-4 mg / mL;

[0074] Solution A is subjected to a hydrothermal reaction at 120-160° C. for 16-32 hours. The solid-liquid mixture after the reaction is collected and first centrifuged and washed with water and then with ethanol, and then dried at 60-80° C. to obtain an organic-modified vanadium oxide composite material.

[0075] The vanadium pentoxide aqueous solution can be purchased or prepared by oneself, and the method of preparing by oneself comprises the following steps:

[0076] Add vanadium pentoxide powder into water and stir to obtain a vanadium pentoxide aqueous solution.

[0077] The purity of vanadium pentoxide will also affect the effect of the above-mentioned hydrothermal reaction. Therefore, in some embodiments, the purity of the vanadium pentoxide powder is 95%~99.99%. Since the preparation process of the above-mentioned organic-modified vanadium oxide composite material has low requirements on the purity of the reactants, commercial V2O5 can be used as a raw material, which is low in cost and suitable for commercial production.

[0078] Stirring can accelerate the dissolution of vanadium pentoxide powder in water. Stirring helps to break the interfacial tension between powder particles and water, so that more water molecules can contact powder particles, thereby accelerating the dissolution rate. Appropriate stirring speed helps to accelerate dissolution or uniform distribution. In some embodiments of the present application, the stirring speed is 200~400r / min, specifically, the stirring speed can be 200r / min, 300r / min, 400r / min, etc. Too fast stirring speed may produce bubbles or foam, affecting the mixing effect. The stirring time can be adjusted according to actual conditions. In some embodiments of the present application, the stirring time is 10~20 min, specifically, the stirring time can be 10min, 15min, 20 min, etc.

[0079] Furthermore, the present invention also proposes the use of an organic-modified vanadium oxide composite material obtained by the preparation method of the organic-modified vanadium oxide composite material in a positive electrode material for an aqueous zinc-iodine battery.

[0080] In practical application, the preparation method of the positive electrode material of aqueous zinc-iodine battery comprises the following steps:

[0081] The organic-modified vanadium oxide composite material provided in the above embodiment is mixed with a conductive agent and a binder, and ground, and mixed with an organic solvent to obtain a slurry;

[0082] The slurry is coated on a current collector and dried to obtain an aqueous zinc-iodine battery positive electrode material.

[0083] In some embodiments, the mass ratio of the organic-modified vanadium oxide composite material, the conductive agent and the binder is (6.5~7):(2~3):(0.5~1). Specifically, the mass ratio of the organic-modified vanadium oxide composite material, the conductive agent and the binder can be 6.5:2:0.5, 6.8:2.5:0.8, 7:3:1, etc.

[0084] The conductive agent is used to improve the conductivity of the electrode material and ensure that the current generated by the active material can be smoothly transmitted to the current collector. In some embodiments, the conductive agent includes at least one of acetylene black, carbon black, conductive carbon black and carbon nanotubes. In addition, other conductive agents can also be used. When the conductive agent uses at least one of acetylene black, carbon black, conductive carbon black and carbon nanotubes, the conductive performance is better.

[0085] The binder is used to bind the active material and the conductive agent to the current collector to prevent them from falling off during the use of the battery. In some embodiments, the binder includes polyvinylidene fluoride, and other binders such as polytetrafluoroethylene can also be used. When the binder uses polyvinylidene fluoride, the bonding performance is better.

[0086] The organic solvent is used to mix the organic modified vanadium oxide composite material, the conductive agent and the binder into a uniform slurry for easy coating. In some embodiments, the organic solvent includes N-methylpyrrolidone. In addition, other organic solvents such as ethanol can also be used. N-methylpyrrolidone not only has good solubility, can be dissolved in water and most other organic solvents, but also has good chemical stability.

[0087] The current collector is used to collect and transmit current. In the positive electrode material of the aqueous zinc-iodine battery, the current collector mainly collects the current generated by the active material and transmits it to the external circuit. In some embodiments, the current collector includes at least one of carbon cloth and stainless steel mesh, and the carbon cloth has the beneficial effects of low resistance and high current transmission efficiency.

[0088] In the specific preparation, the organic modified vanadium oxide composite material and the conductive agent are mixed and ground according to the above ratio, and then polyvinylidene fluoride is added, and then N-methylpyrrolidone is added to form a slurry. Among them, polyvinylidene fluoride is added in the form of a solution, the solvent is N-methylpyrrolidone, and the solute is polyvinylidene fluoride. The concentration of the organic modified vanadium oxide composite material in the slurry is 20~50mg / mL;

[0089] The slurry is mixed evenly and then coated on a carbon cloth current collector, and dried to obtain an aqueous zinc-iodine battery positive electrode.

[0090] Specifically, the concentration of the organic-modified vanadium oxide composite material in the slurry may be 20 mg / mL, 35 mg / mL, 50 mg / mL, etc. Preferably, the concentration of the organic-modified vanadium oxide composite material in the slurry is 20 mg / mL.

[0091] In the technical scheme of the present invention, the prepared organic modified vanadium dioxide positive electrode material is assembled with zinc negative electrode, glass fiber diaphragm soaked with 2 M zinc sulfate and 0.2 M zinc iodide electrolyte into an electrolytic water-based zinc-iodine battery in sequence, and a series of electrochemical performance tests are carried out. At 0.1 A / g, the initial specific capacity of the zinc-iodine battery reaches 338 mAh / g, and the specific capacity of 333 mAh / g can still be maintained after 55 cycles; at a current density of 0.5 A / g, the reversible specific capacity can reach 326 mAh / g, and as the current density increases to 5 A / g and then returns to 0.5 A / g, the positive electrode material exhibits a specific capacity of 330 mAh / g, indicating that it has a stable structure and good rate performance. Therefore, the aqueous zinc-iodine battery positive electrode material prepared by the present invention using the above organic modified vanadium oxide composite material has excellent cycle stability and rate performance.

[0092] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments and drawings. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.

[0093] Example 1

[0094] A method for preparing an organic-modified vanadium oxide composite material comprises the following steps:

[0095] Add 0.364 g of vanadium pentoxide powder to 60 ml of deionized water and stir at 300 r / min for 15 min to obtain a uniform orange vanadium pentoxide aqueous solution;

[0096] Add 0.2088 g of 1,5-diaminonaphthalene powder to the vanadium pentoxide aqueous solution and stir for 30 min to obtain solution A;

[0097] Solution A was transferred to a hydrothermal reactor for hydrothermal reaction at 140°C for 24 h. The solid-liquid mixture in the hydrothermal reactor was collected and centrifuged with water and then with ethanol to obtain a black solid substance, which was dried at 80°C to obtain an organic-modified vanadium oxide composite material.

[0098] Example 2

[0099] A method for preparing an organic-modified vanadium oxide composite material comprises the following steps:

[0100] Add 0.24 g of vanadium pentoxide powder to 60 ml of deionized water and stir at 300 r / min for 15 min to obtain a uniform orange vanadium pentoxide aqueous solution;

[0101] Add 0.12 g of p-aminophenol powder to the vanadium pentoxide aqueous solution and stir for 30 min to obtain solution A;

[0102] Solution A was transferred to a hydrothermal reactor for hydrothermal reaction at 120° C. for 16 h. The solid-liquid mixture in the hydrothermal reactor was collected and centrifuged with water and then with ethanol to obtain a black solid substance, which was dried at 80° C. to obtain an organic-modified vanadium oxide composite material.

[0103] Example 3

[0104] A method for preparing an organic-modified vanadium oxide composite material comprises the following steps:

[0105] Add 0.42 g of vanadium pentoxide powder to 60 ml of deionized water and stir at 300 r / min for 15 min to obtain a uniform orange vanadium pentoxide aqueous solution;

[0106] Add 0.24 g of p-aminophenol powder to the vanadium pentoxide aqueous solution and stir for 60 min to obtain solution A;

[0107] Solution A was transferred to a hydrothermal reactor for hydrothermal reaction at 140° C. for 24 h. The solid-liquid mixture in the hydrothermal reactor was collected and centrifuged with water and then with ethanol to obtain a black solid substance, which was dried at 80° C. to obtain an organic-modified vanadium oxide composite material.

[0108] Example 4

[0109] A method for preparing an organic-modified vanadium oxide composite material comprises the following steps:

[0110] Add 0.2 g of vanadium pentoxide powder to 60 ml of deionized water and stir at 300 r / min for 15 min to obtain a uniform orange vanadium pentoxide aqueous solution;

[0111] Add 0.1 g of 1,5-diaminonaphthalene powder to the vanadium pentoxide aqueous solution and stir for 30 min to obtain solution A;

[0112] Solution A was transferred to a hydrothermal reactor for hydrothermal reaction at 140° C. for 24 h. The solid-liquid mixture in the hydrothermal reactor was collected and centrifuged with water and then with ethanol to obtain a black solid substance, which was dried at 80° C. to obtain an organic-modified vanadium oxide composite material.

[0113] Example 5

[0114] A method for preparing an organic-modified vanadium oxide composite material comprises the following steps:

[0115] Add 0.42 g of vanadium pentoxide powder to 60 ml of deionized water and stir at 300 r / min for 15 min to obtain a uniform orange vanadium pentoxide aqueous solution;

[0116] Add 0.28 g of 1,5-diaminonaphthalene powder to the vanadium pentoxide aqueous solution and stir for 30 min to obtain solution A;

[0117] Solution A was transferred to a hydrothermal reactor for hydrothermal reaction at 140° C. for 24 h. The solid-liquid mixture in the hydrothermal reactor was collected and centrifuged with water and then with ethanol to obtain a black solid substance, which was dried at 80° C. to obtain an organic-modified vanadium oxide composite material.

[0118] The organic modified vanadium oxide composite material prepared in Example 1 was characterized by scanning electron microscopy. The results are as follows: Figure 1 to Figure 6 As shown, Figure 1 This is a scanning electron micrograph of the organic-modified vanadium oxide composite material obtained in Example 1 of the present invention; Figure 2 This is the EDS element distribution diagram of all elements in the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention; Figure 3 This is an EDS element distribution diagram of vanadium (V) element in the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention; Figure 4 This is an EDS element distribution diagram of oxygen (O) element in the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention; Figure 5 This is an EDS element distribution diagram of carbon (C) element in the organic-modified vanadium oxide composite material prepared in Example 1 of the present invention; Figure 6 This is the EDS element distribution diagram of nitrogen (N) in the organic-modified vanadium oxide composite material obtained in Example 1 of the present invention. Figure 1 to Figure 6It can be seen that the organic-modified vanadium oxide composite material prepared in Example 1 exhibits an agglomerated block assembled from short rod-like structures. According to EDS energy spectrum analysis, the V and O main material elements and the C and N guest material elements are evenly distributed, indicating that 1,5-diaminonaphthalene and vanadium dioxide are successfully composited.

[0119] The organic modified vanadium oxide composite material prepared in Example 1 was subjected to an X-ray diffraction test, and the results were as follows: Figure 7 As shown. Figure 7 It can be seen that the organic-modified vanadium oxide composite material prepared in Example 1 exhibits a strong VO2 characteristic peak, corresponding to the standard PDF card, indicating that vanadium dioxide is successfully synthesized, while 1,5-diaminonaphthalene has no corresponding characteristic peak in the X-ray diffraction test due to its non-crystalline structure.

[0120] The scanning electron microscope characterization results of the organic-modified vanadium oxide composite materials prepared in Examples 2 to 5 are similar to those in Example 1, showing agglomerated blocks assembled from short rod-like structures.

[0121] Comparative Example 1

[0122] A method for preparing a vanadium oxide material comprises the following steps:

[0123] Add 0.364 g of vanadium pentoxide powder to 60 ml of deionized water and stir at 300 r / min for 15 min to obtain a uniform orange vanadium pentoxide aqueous solution;

[0124] The vanadium pentoxide aqueous solution was transferred to a hydrothermal reactor for hydrothermal reaction at 140° C. for 24 hours. The solid-liquid mixture in the hydrothermal reactor was collected and centrifuged and washed with water and then with ethanol. The black solid was collected and dried at 80° C. to obtain a vanadium oxide material.

[0125] Comparative Example 2

[0126] A method for preparing a vanadium oxide material comprises the following steps:

[0127] Add 0.364 g of vanadium dioxide powder to 60 ml of deionized water and stir at 300 r / min for 15 min to obtain a uniform vanadium dioxide aqueous solution;

[0128] The vanadium dioxide aqueous solution was transferred to a hydrothermal reactor for hydrothermal reaction at 140° C. for 24 hours. The solid-liquid mixture in the hydrothermal reactor was collected and centrifuged and washed with water and then with ethanol. The black solid was collected and dried at 80° C. to obtain a vanadium oxide material.

[0129] Preparation of positive electrode materials for aqueous zinc-iodine batteries

[0130] The organic modified vanadium oxide composite materials obtained in Examples 1 to 5 and the vanadium oxide materials obtained in Comparative Examples 1 and 2 were used as active materials to prepare positive electrodes for aqueous zinc-iodine batteries according to the following methods:

[0131] 140 mg of active substance and 40 mg of acetylene black were mixed and ground for 30 min, and then 0.4 mL of polyvinylidene fluoride solution was added, and then 6.6 mL of N-methylpyrrolidone was added to form a slurry, wherein the concentration of polyvinylidene fluoride in the polyvinylidene fluoride solution was 50 mg / mL, the solvent in the polyvinylidene fluoride solution was N-methylpyrrolidone, and the concentration of active substance in the slurry was 20 mg / mL;

[0132] The slurry was mixed evenly and then coated on a carbon cloth current collector, and dried in an oven at 80°C to obtain an aqueous zinc-iodine battery positive electrode.

[0133] Preparation of batteries

[0134] The positive electrodes of aqueous zinc-iodine batteries prepared from the active materials provided in Examples 1 to 5 and Comparative Examples 1 to 2 were cut and matched with 150 μm zinc foil to assemble into CR2025 button batteries.

[0135] The button battery structure from bottom to top is: positive electrode shell, positive electrode, glass fiber separator, zinc foil, gasket, shrapnel, negative electrode shell; before the button battery is assembled, 0.2 mL of electrolyte is dripped with a pipette; the electrolyte solutes are ZnSO4 and ZnI2, and the solvent is deionized water; in the electrolyte, the concentration of ZnSO4 is 2 mol / L, and the concentration of ZnI2 is 0.1 mol / L.

[0136] After the battery is assembled, it is compacted by a packaging machine and then subjected to electrochemical testing.

[0137] Electrochemical testing

[0138] 1. Constant current charge and discharge test

[0139] (1) The battery prepared from the organic-modified vanadium oxide composite material prepared in Example 1 and the battery prepared from the vanadium-based oxide material prepared in Comparative Example 1 were subjected to constant current charge and discharge tests at 0.1 A / g. The results are as follows: Figure 8 As shown, when the comparative example 1 is charged to 1.3 V, a voltage platform caused by the shuttling effect of polyiodide ions is exhibited, so that the battery cannot be charged to 1.6 V, and the cyclic charge and discharge under low current cannot be achieved; in Example 1, the introduction of 1,5-diaminonaphthalene can effectively inhibit the generation of polyiodide ion side reactions, and the battery can be charged to 1.6 V, and then the cyclic charge and discharge can be completed normally.

[0140] (2) The vanadium-based oxide material prepared in Comparative Example 1 was subjected to a constant current charge and discharge test at 0.5 A / g. The results are as follows: Fig. 9 As shown in the figure, the number of cycles increases in the direction of the arrow. Although the battery can complete the charge and discharge cycle from 0.4 V to 1.6 V, the charging side reaction platform at 1.3 V gradually extends with the increase of the number of cycles, and the coulombic efficiency decreases, indicating that the battery is gradually seriously affected by the shuttle effect of poly-iodide, reducing the battery life.

[0141] 2. Cycle stability test

[0142] The cycle stability test is a constant current charge and discharge test, which continuously charges and discharges at a charge and discharge rate of 0.1 A / g.

[0143] The battery prepared from the organic modified vanadium oxide composite material prepared in Example 1 was subjected to a cycle charge and discharge test at 0.1 A / g. The results are as follows: Fig.10 As shown in the figure, the initial discharge capacity of the battery is 338 mAh / g, which rises to 373 mAh / g after 5 cycles, and then maintains a capacity of 333 mAh / g after 55 cycles, showing stable cycle performance. In addition, the battery can maintain a high coulombic efficiency of more than 95% during the cycle, indicating that side reactions are suppressed during the charge and discharge process.

[0144] 3. Rate performance test

[0145] The rate performance test was performed by continuous charging and discharging at charge and discharge rates of 0.5, 0.8, 1.0, 2.0, 3.0, 4.0, 5.0 and 0.5 A / g, respectively.

[0146] The rate performance test of the battery prepared by the organic modified vanadium oxide composite material obtained in Example 3 was carried out. The results are as follows: Fig.11 As shown, the composite material has a reversible specific capacity of 328 mAh / g at 0.5 A / g. As the rate increases to 5 A / g, the battery capacity can still be maintained at 174 mAh / g. After the current density returns to 0.5 A / g, the material exhibits a specific capacity of 331 mAh / g, indicating that the composite material not only does not undergo structural collapse due to high current charge and discharge, but also exhibits a higher capacity after activation and has excellent rate performance.

[0147] The above are only preferred embodiments of the present invention, and do not limit the patent scope of the present invention. For those skilled in the art, the present invention may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the patent protection scope of the present invention.

Claims

1. A method for preparing an organic-modified vanadium oxide composite material, characterized in that: The following steps are involved: The vanadium pentoxide aqueous solution and the organic monomer are mixed and stirred to obtain a solution A; Performing a hydrothermal reaction on solution A, collecting the solid-liquid mixture, washing and drying it, and obtaining an organic-modified vanadium oxide composite material; The organic monomer includes at least one of 1,5-diaminonaphthalene, 1,8-diaminonaphthalene, p-aminophenol, m-aminophenol and o-aminophenol.

2. The method for preparing the organic-modified vanadium oxide composite material according to claim 1, characterized in that: In the step of mixing and stirring the vanadium pentoxide aqueous solution and the organic monomer to obtain solution A: The vanadium pentoxide aqueous solution has a vanadium pentoxide concentration of 4-7 mg / mL; and / or, The stirring time is 30 to 60 min; and / or, In the solution A, the concentration of organic monomers is 2-4 mg / mL.

3. The method for preparing the organic-modified vanadium oxide composite material according to claim 1, characterized in that: In the step of subjecting solution A to a hydrothermal reaction, collecting the solid-liquid mixture, washing and drying it, and obtaining an organic-modified vanadium oxide composite material: The temperature of the hydrothermal reaction is 120-160° C.; and / or, The hydrothermal reaction time is 16 to 32 hours; and / or, The drying temperature is 60-80°C.

4. The method for preparing the organic-modified vanadium oxide composite material according to claim 1, characterized in that: Before the step of mixing and stirring the vanadium pentoxide aqueous solution with the organic monomer, the method further comprises: Add vanadium pentoxide powder into water and stir to obtain a vanadium pentoxide aqueous solution.

5. The method for preparing the organic-modified vanadium oxide composite material according to claim 4, characterized in that: The purity of the vanadium pentoxide powder is 95% to 99.99%; and / or, The stirring time is 10 to 20 min; and / or, The stirring speed is 200-400 r / min.

6. Use of an organic-modified vanadium oxide composite material obtained by the preparation method of the organic-modified vanadium oxide composite material as claimed in any one of claims 1 to 5 in a positive electrode material for an aqueous zinc-iodine battery.

7. A method for preparing a positive electrode material for an aqueous zinc-iodine battery, characterized in that: The following steps are involved: The organic modified vanadium oxide composite material is mixed with a conductive agent and a binder, and ground, and mixed with an organic solvent to obtain a slurry; The slurry is applied onto a current collector and dried to obtain an aqueous zinc-iodine battery positive electrode material; Wherein, the organic-modified vanadium oxide composite material is prepared by the preparation method of the organic-modified vanadium oxide composite material according to any one of claims 1 to 5.

8. The method for preparing the positive electrode material for aqueous zinc-iodine batteries according to claim 7, characterized in that: In the slurry, the concentration of the organic-modified vanadium oxide composite material is 20-50 mg / mL.

9. The method for preparing the positive electrode material of aqueous zinc-iodine battery according to claim 7, characterized in that: The mass ratio of the organic modified vanadium oxide composite material, the conductive agent and the binder is (6.5-7): (2-3): (0.5-1); and / or, The conductive agent includes at least one of acetylene black, carbon black, conductive carbon black and carbon nanotubes; and / or, The binder comprises polyvinylidene fluoride; and / or, The organic solvent comprises N-methylpyrrolidone; and / or, The current collector includes at least one of carbon cloth and stainless steel mesh.

Citation Information

Patent Citations

  • Synthetic method for dimension-controllable vanadium dioxide nano material, and lithium ion battery

    CN105836800A

  • VO2.nH2O nano-sheet material, aqueous zinc ion battery positive electrode material and preparation method of aqueous zinc ion battery positive electrode material

    CN115842123A